2021
DOI: 10.48550/arxiv.2106.03086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing the Kerr black hole hypothesis with GRS 1716-249 by combining the continuum-fitting and the iron-line methods

Zuobin Zhang,
Honghui Liu,
Askar B. Abdikamalov
et al.

Abstract: The continuum-fitting and the iron-line methods are currently the two leading techniques for measuring the spins of accreting black holes. In the past few years, these two methods have been developed for testing fundamental physics. In the present work, we employ state-of-the-art models to test black holes through the continuum-fitting and the iron-line methods and we analyze three NuSTAR observations of the black hole binary GRS 1716-249 during its outburst in 2016-2017. In these three observations, the sourc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Our goal is to test the Kerr hypothesis by combining the study of the thermal component and the reflection features. We note that similar studies were reported in Tripathi et al (2021a) and in Zhang et al (2021). Tripathi et al (2021a) analyzed a NuSTAR observation of GX 339-4 in which spectrum simultaneously shows a strong thermal component and prominent reflection features.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our goal is to test the Kerr hypothesis by combining the study of the thermal component and the reflection features. We note that similar studies were reported in Tripathi et al (2021a) and in Zhang et al (2021). Tripathi et al (2021a) analyzed a NuSTAR observation of GX 339-4 in which spectrum simultaneously shows a strong thermal component and prominent reflection features.…”
Section: Discussionsupporting
confidence: 83%
“…This constraint is somewhat weaker than the typical constraints obtained from the analysis of the reflection features with relxill nk; see, e.g., Tab. 5 in Zhang et al (2021). However, it is stronger than the constraint on α 13 inferred by the study of the thermal spectrum of LMC X-1 with nkbb in Tripathi et al (2020b).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The constraints inferred from the 2019 NuSTAR observation of EXO 1846-031 are among the most stringent ones. Slightly stronger constraints can be obtained from three sources in which it is possible to combine the analysis of the reflection features with that of the thermal spectrum: GRS 1716-249 [49], GRS 1915+105 [48], and GX 339-4 [22]. As discussed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…To test GR as a theory of gravity, one of the approaches is to use a parametrized metric and measure possible deviations from the solution of Einstein equations such as the Kerr solution [5][6][7][8]. In the past few years, there have been a number of studies testing the Kerr hypothesis [9] by using X-ray data from NuSTAR, RXTE, Suzaku, and XMM-Newton [10][11][12][13][14][15], GW data from LIGO and Virgo [16][17][18], and radio data from the Event Horizon Telescope (EHT) experiment [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%